INFLUENCE OF EDUCATIONAL LEVELS AND SMALL AND MEDIUM ENTERPRISES PERCEPTION TO USE SAK-ETAP ON SMALL AND MEDIUM ENTERPRISES IN BATAM CITY - haposan banjarnahor; Devi Devi (Jurnal Apresiasi Ekonomi, 2018)
Small-medium enterprises have an important role in Indonesia economy, especially in Batam City. There are few problems in these enterprise, especially in the management of financial statements. This is due to the low level of education and the lack of perceptions of small-medium enterprises. In terms of management of financial statements, the government has issued SAK ETAP (Financial Accounting Standards Entity Without Public Accountanbility) to facilitate small-medium enterprises in managing financial statements. This research is done with the aim to know the influence of education level and perception of small- medium enterprises to the use of SAK ETAP SMEs in Batam City. Data collection techniques with questionnaires distributed to 300 respondent who are samples in this study. Respondent in this study are the small-medium enterprises located in  Batam City. Data analysis using multiple linear regression analysis with  SPSS version 21 software. The coefficient of determination value of this research is  3,6%. The result of t test is that the variable of education level have affect to the use of SAK ETAP equal to 0,003 less than 0,05 and t value 3,000 bigger than t value table 1,9679. While the perception variable does not affect the use of SAK ETAP because 0,219 is greater than 0,05 and the value of t arithmetic 1,231 is smaller than t value table 1,9679. The result of F-test show that the level of education and perception together have affect on the use of SAK ETAP of 0,004 is smaller than 0,05 and the value of F arithmetic 5,522 is greater than F table 3,0258. Key word: Small Medium Enterprises (SME), Education Level, Perception, use of SAK ETAP